Dissociation of H2 on Mg-coated B12C6N6 - 马丽 金雪玲 杨慧慧 王小霞 杜宁 陈宏善 (中国物理B：英文版, 2017)
The dissociation of H2 molecule is the first step for chemical storage of hydrogen, and the energy barrier of the dissociation is the key factor to determine the kinetics of the regeneration of the storage material. In this paper, we investigate the hydrogen adsorption and dissociation on Mg-coated B12C6N6. The B12C6N6 is an electron deficient fullerene, and Mg atoms can be strongly bound to this cage by donating their valance electrons to the virtual 2p orbitals of carbon in the cluster. The preferred binding sites for Mg atoms are the B2C2 tetragonal rings. The positive charge quantity on the Mg atom is 1.50 when a single Mg atom is coated on a B2C2 ring. The stable dissociation products are determined and the dissociation processes are traced. Strong orbital interaction between the hydrogen and the cluster occurs in the process of dissociation, and H2 molecule can be easily dissociated. We present four dissociation paths, and the lowest energy barrier is only 0.11 eV, which means that the dissociation can take place at ambient temperature.